2013
DOI: 10.1007/s00705-013-1953-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the coat protein of olive latent virus 1 isolates

Abstract: The CP gene variability among 21 olive latent virus 1 (OLV-1) isolates obtained from different hosts and locations and at different times was assessed. Amplicons obtained by RT-PCR were cloned, and at least 10 sequences from each isolate were analyzed and compared. OLV-1 sequences available in GenBank were included. The encoded CPs consisted of 270 amino acids, except those of isolates G1S and C7 (269 aa) and G6 (271 aa). Comparison of CP genomic sequences of the isolates under study showed very low values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…Including all Genbank isolates, nucleotide identity between genomes ranged from 100% to 96.55%. Nucleotide diversity between all sequences was 0.01, which is very low for viruses generally and similar to the lowest recorded diversity values in the Tombusviridae (table 1) [24][25][26] .…”
supporting
confidence: 75%
“…Including all Genbank isolates, nucleotide identity between genomes ranged from 100% to 96.55%. Nucleotide diversity between all sequences was 0.01, which is very low for viruses generally and similar to the lowest recorded diversity values in the Tombusviridae (table 1) [24][25][26] .…”
supporting
confidence: 75%
“…Different templates such as TNA, total RNA and dsRNA have been used as viral targets for RT-PCR. The use of dsRNA as a template reduces the constraint caused by the common low viral concentration and uneven distribution in trees, by using large amounts of sample and, at the same time, allowing the elimination of virus non-related nucleic acids that interfere in viral genome amplification (Bertolini et al 2003;Varanda et al 2010;Luigi et al 2011;Varanda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it have been reported that the purifying selection often results in amino acid changes with functional or structural modifications such as genome protection, cell-to-cell movement, transmission between plants, interactions with the host and/or vector, etc. [22].…”
Section: Discussionmentioning
confidence: 99%